Role of Entrepreneurs in Strategy Making Processes in Small Firms - Eswaran, M. B. (Prabandhan: Indian Journal of Management, 2010)
The literature focusing on small firms has increased substantially in the last three decades. Robinson and Pearce (1984), for instance, presented a classification including four research thrusts on small firm strategic planning, namely: (i) Strategic Planning Practices which included papers focusing on the nature of the strategic planning process in small firms, and the decision making approaches adopted by the entrepreneurs; (ii) Value of Planning which considered how strategic planning and performance of small businesses were related; (iii) Specific Features of the Planning Process that focused on specific aspects of strategic planning, such as the search for external information and the use of consultants; and (iv) Content of Strategy that dealt with types of strategy adopted by entrepreneurs in different environment settings.